Miniatuur. (Arnhem : Stichting 6828 KK, Kunst in kwartier, 2000)
Andrew, Eve ; Askjaer Veldt, Marion ; Beks, Elma ; van den Beukel, Adri ; Bodt, Ben ; Dekkers, Josef ; Gerrits, Kassiël ; Gerritsen, Wil ; Grote Beverborg, Ellen ; Hoogland, Francis ; Koop, Jeroen ; van Kleef, Anja ; van Loenhout, Daan ; Loman, Lex ; van Mierlo, Inge ; Najand, Jila ; Najand, Soheila ; Nijman, Martin ; van Ommen, Herman ; van Oosten, Rob ; Overbeek, Madelon ; Peek, Esther ; Peijer, Ton ; Peters, Hans Christiaan ; Philipsen, Gérard J. ; Pil, Martin ; Postma, Marijke ; Rademaker, T. ; Stolker, Judith ; Strik, Maria ; Sueters, José ; Verstegen, Jolanda ; Vis, Ewout ; Wessels, Ditte ; de Wit, Marta ; Wittenberg, Esther
Nederlands
Miniatuur, Stichting 6828 KK, Kunst in kwartier, Arnhem, Mei 2000
boek